Translation of Surah Al-A'laa Version of Dr. Mustafa Khattab and Abdullah Yusuf Ali: A Semantic Analysis - Zalwi, Ikram Abdullah; Zaim, M. (Universitas Negeri Padang, 2024)
Semantic analysis and translation are two interrelated studies in which translation is analyzed in terms of meaning from the source language to the target language so that there is no change in the content of the message or the meaning of the words conveyed. The aim of this study is to analyze the types of meaning and types of lexical relations contained in the English translation of surah Al-A'laa translated by Dr. Mustafa Khattab and Abdullah Yusuf Ali. The data in this study were the words including noun (isim), verb (fi’il) and preposition (huruf) as well as phrases, and sentences contained in the English translation of surah Al-A'laa from verses 1-19. The data were analyzed based on the explanation from the book of Kareem (2023) and Saeed (2016). This research was descriptive research. Based on the data analysis, the researcher found six types of meaning and three types of lexical relations. They were conceptual, connotative, social, affective, reflected and thematic meaning types and the types of lexical relations were synonymy, antonymy and hyponymy.